Co-designing web-based tools for graduate students: a narrative account of a participatory design action research - Laura Iseut Lafrance St-Martin; Émilie Tremblay-Wragg; Sara Mathieu-Chartier (Social Sciences and Humanities Open)
Graduate programs worldwide exhibit a high dropout rate, with numerous contributing factors. Among these, isolation and lack of writing support are significant. This methodological article explores the design process of two web applications supporting graduate students' social and academic needs. It was a collaborative user experience design project involving researchers (including research coordinators), potential users, a non-profit organization, and a web developer. We present the main phases of the study, highlighting the development challenges we faced and their resolutions. The discussion offers six key co-design process lessons to benefit future design research endeavors: 1) take the time to build team cohesion, 2) both types of co-design sessions (knowledge and descriptive) are helpful, but at different moments, 3) do not be afraid to tackle difficult problems with your co-researchers and to admit your limitations, 4) know the co-researchers’ strengths and competencies, 5) fluid communication takes time but is essential and 6) don't be afraid to politically engage your co-researchers.